Gender Pay Gap Lower in Large Cities than in Rural Areas - Anne Busch; Elke Holst (Weekly Report, 2008)
For years, the difference between the gross hourly earnings of women and of men has remained constant for German white-collar employees at about 30 percent. It is obvious that regional factors play an important role in explaining this difference. In rural areas, the gender pay gap is especially pronounced (2006: 33 percent) while in metropolitan areas it is considerably lower than the average (2006: 12 percent). This more favorable ratio is mainly due to the increased employment opportunities for highly-qualified women in cities. In addition, it is evident that where there are high levels of regional unemployment at the county level, women's pay suffers more than men's. The present study was based on the data from the German Socio-Economic Panel Study (SOEP). Focusing on white-collar salaried employees (Angestellte) allows us to analyze pay determinants on the basis of largely homogenous pay structures.
Keywords: J31; J71; J24; 330; Gender paygap; Metropolitan areas; Wage curve; Oaxaca-Blinder-decomposition